The effect of members on charities' annual reporting: evidence from companies limited by guarantee in Australia. (21st August 2021) - Johansson, Elka; Carey, Peter; Tanewski, George; Yusoff, Iliyas
Abstract: In contrast to membership organisations that serve the interest of members, members of charities operating as companies limited by guarantee are responsible by law for ensuring the charity serves its broader charitable purpose. This study examines how members of these large charitable companies discharge accountability through annual report disclosure. We analyse data on 630 company‐year observations for a sample of 153 Australian charitable companies limited by guarantee that lodged annual reports with regulators. Results show that members encourage the disclosure of financial and non‐financial information in the annual report and this in turn influences charities' future donations and grants revenue.